Larch : A Promising Deciduous Conifer as an Eco-Environmental Resource - Koike, Takayoshi (2019)
Larch species are widely distributed in the northern hemisphere where permafrost and seasonal frozen soil exist. This species with heterophyllous shoots has been intensively planted in northeast Asia as well as in northeast China as the principal afforestation species for restoring agricultural lands to forests from 1999. Although approximately 15 species exist in the northern hemisphere and they are easy to hybridize. Among them, Japanese larch grows the fastest and was exported to Europe as a breeding species from early 20s. Although Japanese larch is tolerant to cold, it suffered from various biological stresses. After nearly 40¬†years of vigorous breeding effort, hybrid larch F1 (Dahurian larch √ó Japanese one) was developed with simple propagation methods. With the use of free-air CO2 enriched (FACE) systems, we revealed growth responses of the F1 and its parent larches to environmental conditions. From experiments, F1 showed high responses to elevated CO2 and O3 but not so much to N loading. As future perspectives for larch plantations as an important eco-environmental resource, we expect to afforest F1 seedlings infected with ectomycorrhizae (e.g., Suillus sp.) for efficient afforestation at nutrient-poor sites and at the same time for the production of delicious mushrooms.